Case Report: Gastric submucosal neoplasm with CTNNB1 mutation showing GLI1 overexpression and epithelial differentiation - Karin Ashizawa; Tsuyoshi Saito; Tsuyoshi Saito; Yukinori Yube; Shinji Mine; Tetsu Fukunaga; Cristina R. Antonescu; Takashi Yao (Frontiers in Medicine)
New disease entities have been emerging based on molecular pathological findings, such as pseudoendocrine sarcoma and mesenchymal neoplasm with GLI1 gene alterations, which resemble well-differentiated neuroendocrine tumors. We report a unique case of a gastric submucosal neoplasm of approximately 1.5 cm in size with CTNNB1 mutation showing GLI1 overexpression and epithelial differentiation in a 66-year-old man. It was incidentally identified by routine health screening, and was a slowly growing tumor. Macroscopically, it was a slightly protruded tumor into the mucosa, and was primarily located from the submucosa to the muscularis propria. It was a well-defined lesion measured approximately 20 mm, and was almost stable during almost 5 years after initial identification of the tumor. Uniform round-to-epithelioid cells arranged in solid trabeculae with a microtubular/acinar appearance were seen microscopically. Occasional mitotic figures were noted, but no necrosis was observed. Immunohistochemistry (IHC) demonstrated diffuse expression of pan-cytokeratin, CD10, and CD56 without neuroendocrine markers (chromogranin A, synaptophysin, and INSM1). Molecular analysis confirmed the presence of a hot spot CTNNB1 mutation (S33C), supported by diffuse β-catenin nuclear expression by IHC. Further molecular investigations revealed the absence of GLI1 gene rearrangements, GLI1 amplification, and other fusions. Several differential diagnoses were considered; however, none adequately fit the criteria. The patient remained disease-free for 24 months postoperatively without further adjuvant therapy.